The making of modern Iran : state and society under Riza Shah 1921-1941 - Cronin, Stephanie (RoutledgeCurzon/BIPS Persian studies series., 2003)
The articles in this volume collectively present a picture of Iran under Riza Shah in all its complexity, in darker as well as lighter shades, highlighting the era's debt to the past as well as its legacy to the future.